Extended-Spectrum Beta-Lactamase-Producing Escherichia coli Meningitis and Cerebral Abscess in a Neonate: Therapeutic Challenge - Surasak Puvabanditsin; Marianne Jacob; Maaz Jalil; Samhita Bhattarai; Qaiser Patel; Mehrin Sadiq; Rajeev Mehta (Case Reports in Infectious Diseases)
We report a case of a 12-day-old term neonate with extended-spectrum beta-lactamase (ESBL) producing Escherichia coli (E. coli) meningitis and cerebral abscess. The patient received a 7-day course of antibiotics just few days prior to the infection. The incidence of infections from ESBL-producing E. coli is increasingly emerging. Antimicrobial agents must be vigilantly utilized to prevent the new highly resistant bacteria.